Generation of H11-albumin-rtTA Transgenic Mice: A Tool for Inducible Gene Expression in the Liver - Yu-Shan Li; Ran-Ran Meng; Xiu Chen; Cui-Ling Shang; Hong-Bin Li; Tao-Jun Zhang; Hua-Yang Long; Hui-Qi Li; Yi-Jing Wang; Feng-Chao Wang (G3: Genes, Genomes, Genetics, 2019)
The modification of the mouse genome by site-specific gene insertion of transgenes and other genetic elements allows the study of gene function in different developmental stages and in the pathogenesis of diseases. Here, we generated a “genomic safe harbor” Hipp11 (H11) locus-specific knock-in transgenic mouse line in which the albumin promoter is used to drive the expression of the reverse tetracycline transactivator (rtTA) in the liver. The newly generated H11-albumin-rtTA transgenic mice were bred with tetracycline-operator-Histone-2B-green fluorescent protein (TetO-H2BGFP) mice to assess inducibility and tissue-specificity. Expression of the H2BGFP fusion protein was observed exclusively upon doxycycline (Dox) induction in the liver of H11-albumin-rtTA/TetO-H2BGFP double transgenic mice. To further analyze the ability of the Dox-inducible H11-albumin-rtTA mice to implement conditional DNA recombination, H11-albumin-rtTA transgenic mice were crossed with TetO-Cre and Ai14 mice to generate H11-albumin-rtTA/TetO-Cre/Ai14 triple transgenic mice. We successfully confirmed that the Cre-mediated recombination efficiency was as strong in Dox-induced H11-albumin-rtTA /TetO-Cre/Ai14 mice as in the control albumin-Cre/A14 mice. Finally, to characterize the expression-inducing effects of Dox in H11-albumin-rtTA/TetO-H2BGFP mice in detail, we examined GFP expression in embryos at different developmental stages and found that newly conceived H11-albumin-rtTA/TetO-H2BGFP embryos of Dox-treated pregnant female mice were expressing reporter GFP by E16.5. Our study demonstrates that these new H11-albumin-rtTA transgenic mice are a powerful and efficient tool for the temporally and spatially conditional manipulation of gene expression in the liver, and illustrates how genetic crosses with these new mice enable the generation of complex multi-locus transgenic animals for mechanistic studies.